2021
DOI: 10.1182/blood.2020005216
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order immunoglobulin repertoire restrictions in CLL: the illustrative case of stereotyped subsets 2 and 169

Abstract: Chronic lymphocytic leukemia (CLL) major stereotyped subset #2 (IGHV3-21/IGLV3-21, ~2.5% of all CLL) is an aggressive disease variant, irrespective of the somatic hypermutation (SHM) status of the clonotypic IGHV gene. Minor stereotyped subset #169 (IGHV3-48/IGLV3-21, ~0.2% of all CLL) is related to subset #2 as it displays a highly similar variable antigen-binding site. We further explored this relationship through next-generation sequencing and crystallographic analysis of the clonotypic B cell receptor immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
3
21
0
1
Order By: Relevance
“…We confirmed the somatic R110 mutation and germline configuration of the K16 and YDSD motifs in all four members of family 3 (Supplementary Figure 1). Regarding the heavy chain, two family members (3B and 3C) belonged to the closely related and clinically aggressive subsets #2 and #169, respectively (44). The respective IGHV genes of these heavy chain stereotypic CLL subsets, IGHV3-21 and IGHV3-48, were 97% identical.…”
Section: Familial Cll Shows Consistent Bcr Ig Characteristicsmentioning
confidence: 99%
“…We confirmed the somatic R110 mutation and germline configuration of the K16 and YDSD motifs in all four members of family 3 (Supplementary Figure 1). Regarding the heavy chain, two family members (3B and 3C) belonged to the closely related and clinically aggressive subsets #2 and #169, respectively (44). The respective IGHV genes of these heavy chain stereotypic CLL subsets, IGHV3-21 and IGHV3-48, were 97% identical.…”
Section: Familial Cll Shows Consistent Bcr Ig Characteristicsmentioning
confidence: 99%
“…The clonotypic IGHV3-21 genes bear a variable SHM load, with most cases (~60%-65%) classified as M-CLL (23,25). The SHM patterns in both the heavy and light chains of subset #2 supported antigen pressure, with some SHMs revealed as critical for self-association leading to cell-autonomous signaling (36,46). Relevant to mention, we recently demonstrated that stereotyped subset #169, a minor CLL subset (~0.2% of all CLL), bears striking immunogenetic but also biological and clinical similarities to subset #2 (25).…”
Section: Cll Subset #2mentioning
confidence: 99%
“…Uniquely among B-cell malignancies, CLL has been found to display an alternative mode of cell activation that is independent of antigen and results from homotypic interactions between two different BcR IG molecules ( 34 ). Studies from our group have dissected the molecular basis of cell-autonomous signaling in CLL, revealing distinct modes of homotypic interactions in different CLL subsets ( 36 , 46 ). Particularly for subsets #2 and #169, it has been demonstrated that BcR–BcR interactions critically rely on light chain-mediated contacts, with a specific mutation from the germline sequence in the linker region between the variable and the constant domain of the light chains, namely, the substitution of arginine for glycine (termed R110) in the clonotypic light chain encoded by the IGLV3-21*01 allele (IGLV3-21 R110 ), identified as key to the capacity for homodimerization underlying cell-autonomous signaling ( 36 , 46 ).…”
Section: Cll Subset #2mentioning
confidence: 99%
See 1 more Smart Citation
“…Τα δύο υποσύνολα είναι πολύ όμοια και σε γενετικό επίπεδο, καθώς φέρουν σε εξίσου μεγάλη συχνότητα μεταλλάξεις στο γονίδιο SF3B1 (45% στο υποσύνολο #2, 43% στο υποσύνολο #169) 60,101 . Η ελαφριά αλυσίδα του υποσυνόλου #169 κωδικοποιείται επίσης από το γονίδιο IGLV3-21, έχει την ίδια δομή και φέρει την ίδια αλλαγή στο σημείο σύνδεσης της σταθερής και της μεταβλητής περιοχής με το υποσύνολο #2 87,107 .…”
Section: στερεότυπο υποσύνολο #2 και το συγγενικό υποσύνολο #169unclassified